Single-Nucleotide Polymorphism Associations for Colorectal Cancer in Southern Chinese Population - Li, Fen-xia (Springer-Verlag Berlin Heidelberg, 2012)
OBJECTIVE: Genome-wide association studies (GWAS) have identified 11 loci that influence the risk of developing colorectal cancer (CRC). Given that these studies were conducted in European Caucasian populations, it is not clear whether the results are relevant for populations with different ethnicities. The aim of this study was to examine these associations in a southern Chinese population. METHODS: Eleven single-nucleotide polymorphisms (SNPs), rs12701937, rs16892766, rs7014346, rs6983267, rs719725, rs10795668, rs3802842, rs4444235, rs9929218, rs10411210, and rs961253, were genotyped in 229 CRC patients and 267 controls using the MassArray SNP genotyping system. RESULTS: Evidence of an association with CRC was found for four of the 11 loci. The strongest associations were with rs4444235 and rs961253, with significant odds ratios close to those reported in previous GWAS. Among these four loci, rs719725 and rs4444235 were significantly associated with female gender, rs3802842, rs961253, and rs4444235 with early disease onset, and rs3802842 with later disease onset. However, no associations with CRC risk were detected for six other loci (rs9929218, rs10411210, rs12701937, rs7014346, rs6983267, and rs10795668), and one SNP, rs16892766, was not polymorphic in any of the study participants. CONCLUSION: The rs4444235 and rs961253 loci are strongly associated with the risk of CRC in southern Chinese.